On an improved boron segregation calibration from a particularly sensitive power MOS process. Issue 1 (9th December 2013) - Koffel, S.; Burenkov, A.; Sekowski, M.; Pichler, P.; Giubertoni, D.; Bersani, M.; Knaipp, M.; Wachmann, E.; Schrems, M.; Yamamoto, Y.; Bolze, D.; Cristiano, Fuccio; et al.
Abstract One of the main issues for the simulation of MOS transistors is the correct prediction of threshold voltages that depend on the active doping profiles in the channel under the gate oxide. Simulating a power MOS process we encountered a situation in which Sentaurus Process with default models failed to predict threshold voltages by as much as 3 V. An in‐depth investigation revealed that the threshold voltage in our pMOS devices is determined by a very special distribution of the doping in the channel that involves both n‐type and p‐type doping which nearly compensate each other. As threshold voltages were found in the simulations to be particularly sensitive to boron segregation, silicon samples were implanted with boron and oxidized in several atmospheres for a variety of process times. The profiles were studied by advanced SIMS methods. Because of the limitations of the SIMS depth resolution, they had to be complemented by electrical measurements on MOS transistors. This combination finally allowed finding a new calibration for the segregation models which allows predicting the electrical characteristics of the transistors in a wide range of experimental conditions. Since the threshold voltage in our transistors turned out to be extremely sensitive to the boron segregation parameters, in contrast to technologies in which only one dopant type prevails, the newly achieved calibration should be superior to previous work. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)